2021
DOI: 10.1080/10826084.2021.1883662
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Substance Misuse among Adolescent and Young Adult Gabapentinoid Users: A Register-Based Follow-up Study of Former Adolescent Psychiatric Inpatients

Abstract: Aims: Our study examined characteristics of adolescent and young adult study participants using gabapentinoids (gabapentin, pregabalin), with previous history of adolescent psychiatric inpatient hospitalization. Particular focus was on temporal association of age, at first prescription for gabapentinoids, to age at tobacco smoking initiation, regular alcohol use, diagnosis of substance dependence and prescriptions for benzodiazepines and opioids. Methods: The initial study population contained 508 adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This is an interesting finding, considering that Peltokorpi et al. (2021) found that tobacco smoking and alcohol use, the first prescriptions of benzodiazepines and opioids, and a diagnosis of substance dependence predated the first prescriptions of gabapentinoids. Our finding indicates that gabapentinoids may challenge the field of prescribing medications, when the “opioid crisis” (Volkow & Blanco, 2021) and misuse of benzodiazepines (Votaw et al., 2019) have been one of the major concerns in worldwide public health in the past decades.…”
Section: Discussionmentioning
confidence: 78%
“…This is an interesting finding, considering that Peltokorpi et al. (2021) found that tobacco smoking and alcohol use, the first prescriptions of benzodiazepines and opioids, and a diagnosis of substance dependence predated the first prescriptions of gabapentinoids. Our finding indicates that gabapentinoids may challenge the field of prescribing medications, when the “opioid crisis” (Volkow & Blanco, 2021) and misuse of benzodiazepines (Votaw et al., 2019) have been one of the major concerns in worldwide public health in the past decades.…”
Section: Discussionmentioning
confidence: 78%
“…6,21 Moreover, gabapentinoid use has also been associated with increased risks of suicidal ideation and behaviour, particularly among adolescents and young adults (15-24 years) and women. [22][23][24] Furthermore, physical dependence, tolerance and withdrawal from gabapentinoids have been well documented at both recommended dosages and supratherapeutic dosages. 6,22,25,26 In cases where a drug is no longer needed or is associated with more harm than benefits, the medicine should cease (or reduce in dose).…”
Section: Introductionmentioning
confidence: 99%
“…benzodiazepines) and opioid analgesics significantly increases adverse events, such as respiratory depression and mortality 6,21 . Moreover, gabapentinoid use has also been associated with increased risks of suicidal ideation and behaviour, particularly among adolescents and young adults (15–24 years) and women 22–24 . Furthermore, physical dependence, tolerance and withdrawal from gabapentinoids have been well documented at both recommended dosages and supratherapeutic dosages 6,22,25,26 …”
Section: Introductionmentioning
confidence: 99%